SQL Server 2008 Query Performance Tuning Distilled - Dam, Sajal; Fritchey, Grant (Apress : Imprint: Apress, 2009)
SQL Server 2008 Query Performance Tuning Distilled presents a direct trouble-shooting methodology for identifying poorly-performing stored procedures and queries, isolating the causes of that poor performance, and fixing the underlying problems. Each chapter is dedicated to one of the top causes of poorly performing queries and shows methods for identifying and dealing with the problems in that chapter's domain. Emphasis is always put upon or placed upon practical methods that you can put to immediate use in your day-to-day work. SQL Server 2008 functionality, tips, and tricks are emphasized in each subject area. Emphasizes the practical. Does not bury readers in theory. Gives readers practical techniques to immediately apply in their daily work. Dedicates a chapter to each of the most common, performance-related problem areas.